Risk of Severe Illness and Risk Factors of Outcomes of COVID-19 in Hospitalized Patients with Chronic Liver Disease in a Major U. S. Hospital Network. (3rd November 2022) - Krishnan, Arunkumar; Prichett, Laura; Liu, Yisi; Ting, Peng-sheng; Alqahtani, Saleh A.; Kim, Amy K.; Ma, Michelle; Hamilton, James P.; Woreta, Tinsay A.; Chen, Po-Hung
Abstract : Background and Aim . Underlying comorbidities are an emerging risk factor for more severe coronavirus disease 2019 (COVID-19). However, its impact on patients with chronic liver disease (CLD) remains unclear. In addition, there is a paucity of data about whether patients with CLD have an increased risk of requiring intensive care, vasopressor support, or mechanical ventilation (MV). This study aimed to evaluate the impact of pre-existing LD on the clinical outcome of hospitalized patients with COVID-19. Methods . We studied 2731 patients with known CLD who were hospitalized at the Johns Hopkins Health System with COVID-19 between March 1, 2020, and December 15, 2021. The primary outcome was all-cause mortality, and secondary outcomes were MV and vasopressors. Multivariable Cox regression models were performed to explore factors associated with the outcomes. Results . Overall, 80.1% had severe COVID-19, all-cause mortality was 8.9%, 12.8% required MV, and 11.2% received vasopressor support. Older patients with underlying comorbidities were more likely to have severe COVID-19. There was association between elevated aminotransferases and total bilirubin with more severe COVID-19. Hepatic decompensation was independently associated with all-cause mortality (HR 2.94; 95% CI 1.23–7.06). Alcohol-related liver disease (ALD, HR 2.79, 95% CI, 1.00–8.02) was independently associated with increased risk for MV, and independent factors related to vasopressor support were chronic pulmonary disease and underlying malignancy. Conclusions . COVID-19 infection in patients with CLD is associated with poor outcomes. SARS-CoV-2 infection in patients with hepatic decompensation was associated with an increased risk of in-hospital mortality hazard, and ALD among patients with COVID-19 was associated with an increased hazard for MV.